Analysis of Cellular Mutants Resistant to Theiler’s Virus Infection: Differential Infection of L929 Cells by Persistent and Neurovirulent Strains - Jnaoui, Karima (American Society for Microbiology, 1999)
Theiler’s murine encephalomyelitis virus (TMEV) is a natural pathogen of the mouse and belongs to the Picornaviridae family. TMEV strains are divided into two subgroups on the basis of their pathogenicity. The first group contains two neurovirulent strains, FA and GDVII, which cause a rapid fatal encephalitis. The second group includes persistent strains, like DA and BeAn, which produce a biphasic neurological disease in susceptible mice. Persistence of these viruses in the white matter of the spinal cord leads to chronic inflammatory demyelination. L929 cells, which are susceptible to TMEV infection, were subjected to physicochemical mutagenesis. Cellular clones that became resistant to TMEV infection were selected by viral infection. Three such mutants resistant to strain GDVII were characterized to determine the step of the virus cycle that was inhibited. The mutation present in one of these mutant cell lines inhibited, by more than 1,000-fold, the entry of strain GDVII but hardly decreased infection by strain DA. In the two other cellular mutants, replication of the viral genome was slowed down. Interestingly, one of these mutant cell lines resisted infection by both the persistent and neurovirulent strains while the second cell line resisted infection by strain GDVII but remained susceptible to the persistent virus. These results show that although they have 95% identity at the amino acid sequence level, neurovirulent and persistent viruses use partly distinct pathways for both entry into cells and genome replication.